Static bioassay with Liza parsia exposed to DDVP, an organophosphate - Mohapatra, B C; Noble, A (Indian Journal of Fisheries, 2011)
DDVP, a water-soluble organophosphate insecticide, is widely used in the Kolleru region of Andhra Pradesh for the control of ectoparasites, such as Lernea and Argulus, on fishes (Muthu el al. 1988). DDVP is used as medicine in salmon farming against the sea lice. The use of this chemical in salmon fanning, however, appears to have deleterious effects on marine invertebrates (Egidius and Moester 1987). Stephanie Pain (1989) linked the epidemic of eye disease in salmon of the wild to the use of this chemical in farms. Acute toxicity tests of DDVP were, therefore, conducted on Liza parsia. Among mullets, Liza parsia, along with Mugil cephalus, has gained considerable importance in fish culture because of its resistance to environmental changes and easy availability. It was, therefore, selected for this study.